Factors Influencing the Consumption Behaviour of Non-Alcoholic Drinks in Vietnam - Nguyen, To The; Bao, Nguyen Duc; Chinh, Hoang Duc; Vuong, Vu Tien; Tuan, Nguyen Anh; Phuong Anh, Nguyen Thi; Lan Huong, Nguyen Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2022)
The paper analyzes consumer behavior towards the choice between green tea and carbonated drinks. We collected 339 valid responses for our probit model. The results indicate six factors influencing the preference between the two types of drinks, with a decreasing impact as follows: age, sex, weekly expenditure for drinks, marital status, and the safety level of tea and carbonated drinks. This paper also shows that if customers’ age decreases by one unit, their preference for carbonated drinks will decrease by 10%; and male customers like carbonated drinks more than female customers. Hence, it provides an overview of the current consumption status of carbonated beverages and green tea, thereby assisting businesses in developing new products suitable for consumers’ tastes.